The investigation of avalanche patterns on railroad tracks with steep slopes - Afriani, Lusmeilia; Iswan, Iswan (Fakultas Teknik UB, 2020)
This study aims to investigate the pattern of landslides on the cliffs forming the railway with steep slopes. This research was conducted at Rejosari Natar Station, South Lampung Regency, Lampung Province. The point of observation is at STA 30 + 250. The data in this study were divided into primary and secondary data. Primary data is the data that is directly obtained in the field by taking soil samples which are then processed in the laboratory. The secondary data is the soil characteristics data of the railroad structure starting from the rail load, rail bearings, ballast layers, sub-ballast layers, and sub-grade. These will be used as input in conducting railroad analysis using Plaxis modelling. Plaxis modeling requires these variables and parameters to be analyzed based on the amount of vertical settlement, total stress, and safety factor values that occur due to rail loads. Reserach found that the value of the soil safety factor was <1.25. This means that the soil condition is in a critical condition for collapse and the ground will experience landslides which can endanger the safety of the passing trains. For this reason, improvements are needed in the soil that will experience landslides